Effectiveness of the repellent of kawista leaf extract (Limonia acidissima) against Aedes aegypti mosquitoes - Qotrinnada, Nabilah; Lukiyono, Yauwan Tobing; Prayekti, Endah; Nidianti, Ersalina (Environmental and Toxicology Management, 2023)
Synthetic insecticides containing highly effective active substances such as DEET (N,N-diethyl-meta toluamide) to prevent and control Dengue Hemorrhagic Fever can have adverse effects on health and the environment. Kawista leaves (Limonia acidissima) have the potential as a natural insecticide against Aedes aegypti mosquitoes because they contain secondary metabolite compounds namely phenols, flavonoids, saponins, and terpenoids. This study aims to determine the effectiveness of the repellent power of kawista leaf extract (Limonia acidissima) against Aedes aegypti mosquitoes. This study used experimental method with post-test only control group design. The sample used was 25 adult of Aedes aegypti mosquitoes in each treatment. The ethanol extract of kawista leaves was made in the form of a spray with a concentration of 25%, 50% concentration, and 75% concentration. The 25% concentration, 50% concentration, and 75% concentration of kawista leaf extract have an effective repellent power against Aedes aegypti mosquitoes, namely 15.22%, 46.20%, and 70.08%, respectively. The results of the analysis of kawista leaf extract against Aedes aegypti mosquitoes obtained ED50 (Effective Dose 50) at a concentration of 60.343% and ED99 (Effective Dose 99) at a concentration of 124.452%. From the results of the study, it can be concluded that kawista leaves have the ability to repel Aedes aegypti mosquitoes.